Emergency resection of a congenital hepatoblastoma: A case report - Kenta Ogasawara; Takeshi Hirabayashi; Tamotsu Kobayashi; Takeshi Saito; Keinosuke Ishido; Kenichi Hakamada (Elsevier, 2024)
Introduction: A congenital hepatoblastoma (CH) is a rare liver tumor that can lead to severe outcomes due to unexpected rapid tumor growth. We report a case of CH with respiratory and circulatory failure caused by tumor growth, in which the patient underwent an emergency tumor resection and survived. Case presentation: A male fetus was diagnosed by fetal ultrasound with a giant abdominal mass at 34 weeks and 5 days of gestation. On the same day he developed fetal distress was delivered by emergency Caesarean section. His birthweight was 3060 g, and his Apgar scores were 4 at 1 minute and 5 at 5 minutes. Immediately after birth he developed respiratory and circulatory failure due to compression of the thoracic organs by the giant abdominal mass. He was intubated shortly after birth and cared for in the intensive care unit. Alpha-fetoprotein (AFP) was 484,000 ng/mL (Normal range: 15,700 to 146,500 ng/mL). A contrast-enhanced computerized tomography (CT) revealed a tumor with a maximum diameter of 150 mm in the right lobe of the liver, suspicious for a congenital hepatoblastoma (CH). His clinical status deteriorated abruptly so he underwent an emergency right liver lobectomy. During the procedure, he developed cardiopulmonary arrest and the tumor was grossly resected while on chest compressions. He was resuscitated and the surgical bed was left with packed gauze. He gradually improved and the packing was removed on postoperative day 10. Pathology confirmed CH. He gradually recovered and was discharged home at 4 months of age. At 8 months of age a recurrence was diagnosed based on rising levels of AFP. He underwent a resection of the recurrence followed by adjuvant chemotherapy. He is free of further recurrence at 2 years of age. Conclusion: Emergency resection of large CH is a high-risk operation but can potentially lead to survival, even if the margins are not tumor-free. Close follow up is mandatory.